Repressive Political Communication through Legal Products to Preserve Ideology of Jokowi's Government - arianto, oni dwi; Sujoko, Anang; Wahyudi, Agus (The Journal of Society and Media, 2021)
The fundamental value of democracy is civil liberties to express an opinion, assembly, and organization. Data from various institutions observing Indonesian democracy show that since Jokowi's leadership, Indonesia has had problems with civil liberties, from previously free to partly free, thus falling into the flawed category of democracy. The decline in civil liberties was triggered by the Jokowi administration's repressive political communications manifested in the form of repressive legal products. These repressive legal products are used to suppress critical opposition groups who are at odds with the Jokowi administration. This study uses a critical paradigm based on qualitative methods that utilize the theory of Political Discourse Analysis (PDA). The research objective is to reveal the various repressive legal products of the Jokowi administration as well as to explain the context, history, power, and ideology behind the production of these repressive laws. The object of study related to repressive legal products is limited to online news published by media verified by the Press Council. The results of the study concluded that the Jokowi administration presented repressive legal products to perpetuate power and smooth the implementation of capitalist neoliberal ideology.